Determinan Forward-Looking Disclosure Pada Perusahaan Manufaktur - Elisa Oktavia; Elsa Imelda (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to analyze the determinants of forward-looking disclosure, such as gender diversity, board size, independent board composition, profitability, firm size, and leverage. This research was conducted by using 287 samples of manufacturing companies listed on the Indonesia Stock Exchange during the period of 2017-2019, using purposive sampling method and processed using multiple regression analysis what helped by EViews 11 software. The results showed that the variables gender diversity, firm size, and leverage had a significant effect on forward-looking disclosure. The implication of this research is the need for careful consideration in applying forward-looking disclosure related to the risk and certainty of the information disclosed, one of which is by reducing the liabilities held to reduce the risks held, but there is a need to increase the application of forward-looking disclosure as a means of communication with stakeholders and to get funding sources.